The eloquence of addressing in the novels of Naguib Mahfouz - Kazem, Zahraa; Mohi, Anaam (Al-Adab Journal, 2023)
If the writer is concerned with all the details of his literary work in order to ensure his literary status, his attention to the title occupies his mind as it is the first thing the reader receives from the text. On the functional purpose of its establishment, rather, it also leads to its significance for the functional purpose of its establishment, for this reason the painters undertake the design of the architectural facades because they represent a painting that tops the architectural edifice, and is linked to it. The novelists who chose the titles of their works well, the choice does not come spontaneously, but depends primarily on his novelistic and rhetorical vision in order to highlight the content of the text, and then deliberately arouse the curiosity of the recipient and his desire to reveal his secrets and secrets through his reliance on displacement, paradox and contradiction